2017
DOI: 10.1159/000479682
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum TSH and Anti-Thyroglobulin Antibody Levels on Lymph Node Fine-Needle Aspiration Thyroglobulin Measurements in Differentiated Thyroid Cancer Patients

Abstract: Background: Thyroglobulin measurements in the washout of fine needle aspiration (FNA-Tg) are an excellent tool to detect lymph node (LN) metastases of differentiated thyroid carcinoma (DTC). Nevertheless, how to define the best cutoffs and the influence of potential confounders are still being discussed. Objective: To evaluate the accuracy of FNA-Tg measurement to detect DTC metastases and the influence of thyroid status and anti-thyroglobulin antibodies (TgAb). Methods: One hundred thirty-eight patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
4
24
2
1
Order By: Relevance
“…66,74 However, if lymph node aspirate is diluted over 50-fold, the Tg-Ab is nearly undetectable and cannot interfere with LN-FNA-Tg measurement even in the presence of sTg-Ab. 19,23,54,60 Based on meta-analysis and literature review, LN-FNA-Tg still maintains with excellent sensitivity and specificity for LNM even in presence of the sTg-Ab. Therefore, the ATA and ETA thyroid cancer treatment guidelines highly recommend using LN-FNA-Tg to diagnose LNM.…”
Section: Clinical Application Of the Preoperative And Postoperativementioning
confidence: 99%
“…66,74 However, if lymph node aspirate is diluted over 50-fold, the Tg-Ab is nearly undetectable and cannot interfere with LN-FNA-Tg measurement even in the presence of sTg-Ab. 19,23,54,60 Based on meta-analysis and literature review, LN-FNA-Tg still maintains with excellent sensitivity and specificity for LNM even in presence of the sTg-Ab. Therefore, the ATA and ETA thyroid cancer treatment guidelines highly recommend using LN-FNA-Tg to diagnose LNM.…”
Section: Clinical Application Of the Preoperative And Postoperativementioning
confidence: 99%
“…In multiple studies, however, high serum TgAb levels showed no interference with FNA-Tg sensitivity [ 52 , 53 ]. Duval et al [ 54 ] reported that the measurement of FNA-Tg is useful for evaluating suspicious lymph nodes in patients with DTC, regardless of TgAb. Boi et al [ 53 ] measured TgAb levels in FNA washout fluid in a limited number of patients, and found that TgAb was undetectable in patients with negative serum TgAb, but a small number of patients with positive serum TgAb (two of eight) showed positive TgAb in washout fluid.…”
Section: Fna Washout Tg and Serum Tgab Levelsmentioning
confidence: 99%
“…типы карцином (недифференцированные раки щитовидной железы) с низкой экспрессией ТГ, определяемой степенью дифференцировки опухолевой ткани. Данный метод может быть особенно эффективен в случаях метастазов с кистозной дегенерацией или иных случаях малоинформативного цитологического заключения, кроме того, на результаты исследования не влияет уровень циркулирующих АТ-ТГ, что определяет его высокую диагностическую точность [25]. Поскольку на результаты исследования не влияет также наличие интактной тиреоидной ткани, он может быть использован в скрининге метастазов как у пациентов, повергшихся оперативному лечению, так и перед подготовкой к нему для установления стадии опухолевого процесса.…”
Section: обсуждение основного результата исследованияunclassified